Physico Chemical Analysis of Wastewater in Perspective of Sustainable Development for an Urban Agglomeration in India and Nigeria (Prakriti - The International Multidisciplinary Research Journal, 2025)
Urban wastewater in Kota, Rajasthan, primarily arises from power plants and manufacturing industries, posing significant challenges due to industrial discharge and rapid urbanization. In contrast, Bauchi Metropolis in northeastern Nigeria is a rapidly growing city with diverse agricultural, commercial, and small-scale industrial activities but struggles with inadequate wastewater infrastructure for collection and treatment. Sustainable development, which seeks to balance environmental, economic, and social goals, requires collaboration among government, businesses, and individuals to foster long-term changes. Both cities must adopt localized and scalable wastewater treatment solutions, enhance infrastructure, and ensure regulatory compliance. Collaborating with international organizations and embracing innovative solutions will be essential for improving water quality and ensuring sustainable urban growth. This study analyzed water samples from both cities during winter and summer seasons, focusing on water quality parameters. The results revealed significant seasonal variations: in India, domestic wastewater pH dropped from 5.22 in winter to 2.22 in summer, while BOD in Nigeria increased from 8.04 mg/L to 8.45 mg/L. DO show a slight increase in India, reaching 8.0 mg/L for industrial wastewater in summer. Turbidity in Nigeria’s domestic wastewater decreased from 357.4 NTU to 180.3 NTU in summer. Hardness was higher in winter, particularly in India’s industrial wastewater at 105 mg/L, while no significant seasonal differences were observed in density. Higher values for electrical conductivity, chloride ion concentration, and calcium hardness were noted in winter. Correlation analysis identified relationships among the analyzed parameters, guiding the selection of appropriate wastewater treatment methods for implementation in treatment plants.
Keywords: Sustainable De velopment; Wastewater Treatment; Kota; Bauchi Metropolis; physico-chemical analysis; BOD; COD and Turbidity